2014
DOI: 10.1104/pp.114.245951
|View full text |Cite
|
Sign up to set email alerts
|

Polar Auxin Transport Is Essential for Medial versus Lateral Tissue Specification and Vascular-Mediated Valve Outgrowth in Arabidopsis Gynoecia

Abstract: Although it is generally accepted that auxin is important for the patterning of the female reproductive organ, the gynoecium, the flow as well as the temporal and spatial actions of auxin have been difficult to show during early gynoecial development. The primordium of the Arabidopsis (Arabidopsis thaliana) gynoecium is composed of two congenitally fused, laterally positioned carpel primordia bisected by two medially positioned meristematic regions that give rise to apical and internal tissues, including the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
121
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 69 publications
(130 citation statements)
references
References 64 publications
8
121
1
Order By: Relevance
“…1A), DR5::RFP marks the two lateral foci and is strongest in the apical-most cells (until about 10 mm below the apex; Fig. 1, B, and D to G), as previously shown (Larsson et al, 2014). In the same tissues, TCSn::GFP is expressed in both apical and subapical medial cells, peaking in expression between 10 mm and 15 mm below the apex (Fig.…”
Section: Cytokinin and Auxin Signaling Act In Mutually Exclusive Domamentioning
confidence: 53%
See 4 more Smart Citations
“…1A), DR5::RFP marks the two lateral foci and is strongest in the apical-most cells (until about 10 mm below the apex; Fig. 1, B, and D to G), as previously shown (Larsson et al, 2014). In the same tissues, TCSn::GFP is expressed in both apical and subapical medial cells, peaking in expression between 10 mm and 15 mm below the apex (Fig.…”
Section: Cytokinin and Auxin Signaling Act In Mutually Exclusive Domamentioning
confidence: 53%
“…In later stage 7 and stage 8, TCSn::GFP becomes restricted to the basal part of the gynoecium, predominantly in the adaxial medial domain, and DR5::RFP expands to the lateral and medial preprocambial domains (Fig. 1, N to P) as previously described for DR5rev::3xVENUS (Larsson et al, 2014), remaining complementary to the observed cytokinin signaling peaks. After 24 h BAP treatment, We have previously shown that blocking PAT in early stage gynoecia with 1-napthylphthalamic acid (NPA) results in an expansion of medially expressed reporters (pSHP2::YFP and TAA1::TAA1::GFP), and a reduced expression of the abaxial lateral reporter pFIL:: GFP, indicating that PAT is important in early stages for correct tissue identity (Larsson et al, 2014).…”
Section: Cytokinin and Auxin Signaling Act In Mutually Exclusive Domamentioning
confidence: 72%
See 3 more Smart Citations